2015
DOI: 10.1016/j.applthermaleng.2014.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and simulation of intensified absorber for post-combustion CO2 capture using different mass transfer correlations

Abstract: This paper studied mass transfer in rotating packed bed (RPB) which has the potential to significantly reduce capital and operating costs in post-combustion CO2 capture. To model intensified absorber, mass transfer correlations were implemented in visual FORTRAN and then were dynamically linked with Aspen Plus ® rate-based model. Two sets of mass transfer correlations were studied and compared through model validations. The second set of correlations performed better at the MEA concentrations tested as compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…Kang et al (2014 and modelled the RPB absorber in gPROMS ® . Joel et al (2014Joel et al ( , 2015 and 2017) simulated RPB absorber and stripper in ASPEN PLUS ® by using FORTRAN ® routines to insert some correlations that were not available in ASPEN PLUS ® . The results of these studies are valuable and different aspects of RPB system were studied.…”
Section: Review Of Previous Studies On Rpb Absorber Modellingmentioning
confidence: 99%
“…Kang et al (2014 and modelled the RPB absorber in gPROMS ® . Joel et al (2014Joel et al ( , 2015 and 2017) simulated RPB absorber and stripper in ASPEN PLUS ® by using FORTRAN ® routines to insert some correlations that were not available in ASPEN PLUS ® . The results of these studies are valuable and different aspects of RPB system were studied.…”
Section: Review Of Previous Studies On Rpb Absorber Modellingmentioning
confidence: 99%
“…The correlation was found to be valid for different sizes of the RPBs and for viscous Newtonian and non-Newtonian fluids. Because of these advantages, Equation 16 is selected for calculating the liquid phase mass transfer coefficient, and also findings from Joel et al [22] suggested the use of Equation 16…”
Section: Gas and Liquid Phase Energy Balancesmentioning
confidence: 99%
“…Study of intensified absorber was reported in Joel et al [21,22] and Agarwal et al [23]. Joel et al [21] reported 12 times volume reduction for absorber if using RPB technology as compared to packed column.…”
Section: Introductionmentioning
confidence: 99%
“…Due to lack of experimental data at these conditions, generating correlations from CFD simulation data could be an effective and economical alternative to meet the requirement of accurate prediction of the performance of the RPB for CO 2 capture. Among the existing correlations, the Burns correlation (Burns et al, 2000) describes the relationship between liquid holdup ( ) and the centrifugal acceleration (g), liquid superficial velocity (U) and viscosity ( ), which is concise and clear, and it has been adopted in many cases (Joel et al, 2015;Joel et al, 2014Joel et al, , 2017Kang et al, 2014;Thiels et al, 2016). Therefore, a similar expression has been adopted to regress the correlations for , A e and A s in the RPB with an expanded mesh packing based on the CFD simulation results.…”
Section: Effect Of the Contact Anglementioning
confidence: 99%